Measuring Financial Cycles in a Model-Based Analysis: Empirical Evidence for the United States and the Euro Area - Gabriele Galati; Irma Hindrayanto; Siem Jan Koopman; Marente Vlekke (Tinbergen Institute, 2016)
We adopt an unobserved components time series model to extract financial cycles for the United States and the five largest euro area countries over the period 1970 to 2014. We find that credit, the credit-to-GDP ratio and house prices have medium-term cycles which share a few common statistical properties. We show that financial cycles are longer and more ample than business cycles, and that their length and amplitude vary over time and across countries.
Keywords: C22; C32; E30; E50; E51; G01; 330; unobserved components time series model; Kalman filter; maximum likelihood estimation; band-pass filter; medium-term cycles